Didactic Design Understanding the Concept of Building Flat with Concrete Objects - Purnomo, Dian; Risnawati; M. Fikri Hamdani (Global Action and Education for Society, 2026)
Understanding the concept of flat building is one of the basic competencies that is very important in learning mathematics in elementary school because it is the foundation for geometry material at the next level, but unfortunately, many students still have difficulty in recognizing, distinguishing, and understanding the properties of various forms of flat building thoroughly. These difficulties are often caused by learning approaches that are too abstract, lack of use of concrete media, and lack of active involvement of students in the meaningful learning process. This research aims to design a didactic design that facilitates the understanding of the concept of flat building through the use of concrete objects. The research method used is didactic design research with a qualitative approach. The research subjects consisted of grade IV elementary school students. Data was collected through observation, interviews, and documentation of student learning outcomes. The results of the study show that the use of concrete objects such as geometrically shaped pieces of paper, and everyday objects is able to help students understand the characteristics of building flat visually and tactily. The didactic design developed contains three stages, namely the stage of initial didactic situation analysis (prospective analysis), the stage of implementing didactic design in the classroom (metapedagogical), and the stage of retrospective analysis. These findings suggest that concrete object-based learning is effective in improving conceptual understanding and reducing students' misconceptions about flat builds. The implications of this research can be used as a reference for teachers in designing meaningful and contextual mathematics learning.